1998
DOI: 10.1017/s0952836998009807
|View full text |Cite
|
Sign up to set email alerts
|

Sodium, net acid and ammonia fluxes in freshwater-adapted European flounder (Platichthys flesus L.). Pharmacological inhibition and effects on gill ventilation volume

Abstract: Net branchial sodium uptake, and net acid and ammonia excretion, together with gill ventilation volumes were measured in euryhaline European¯ounder Platichthys¯esus, adapted to freshwater. External amiloride or acetazolamide (0.1 mmol l -1 ) caused signi®cant reductions (P < 0.05) in sodium uptake and net acid excretion, while 0.05 mmol l -1 thiocyanate had no effect on any of the¯uxes measured. Ethoxzolamide (0.1 mmol l -1 ) however, caused signi®cant reductions in all¯uxes measured and also caused a 32% redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Again, the mechanisms involved may differ between freshwater and seawater fish. Studies in freshwater fish have proposed active export of protons by an apical V-type H ϩ -ATPase, coupled to an import of Na ϩ ions via an ENaC (epithelial Na ϩ -channel)-like channel (10,28). In seawater fish, use of the Na ϩ /H ϩ exchanger and the existing Na ϩ gradient is energetically cheaper.…”
Section: Zoarces Viviparus; Namentioning
confidence: 99%
“…Again, the mechanisms involved may differ between freshwater and seawater fish. Studies in freshwater fish have proposed active export of protons by an apical V-type H ϩ -ATPase, coupled to an import of Na ϩ ions via an ENaC (epithelial Na ϩ -channel)-like channel (10,28). In seawater fish, use of the Na ϩ /H ϩ exchanger and the existing Na ϩ gradient is energetically cheaper.…”
Section: Zoarces Viviparus; Namentioning
confidence: 99%
“…Current hypotheses include a direct coupling through Na + /NH 4 + exchangers, coupling with H + excretion by an apical Na + /H + exchanger (NHE), and coupling with H + excretion via an apical H + pump, which energizes Na + uptake through a putative Na + channel. The last two mechanisms would acidify the gill boundary layer, thereby enhancing the 'diffusion-trapping' of NH 3 as NH 4 + and maintaining the partial pressure gradient for diffusive NH 3 efflux, thus manifesting as an apparent Na + /NH 4 + exchange (Clarke and Potts, 1998;Wilson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Proton equivalent excretion in this study was found to be sensitive to vanadate, and also to the carbonic anhydrase inhibitor acetazolamide (Clarke & Potts, 1998). The titratable component measured in this study did indeed increase upon sodium channel inhibition before eventually declining, although these changes were not signi®cant possibly due to the small sample size.…”
Section: In Vivo Experimentsmentioning
confidence: 45%
“…Proton pumps (H + -ATPase) remove protons from the cell generating a negative potential on the inner side of the apical membrane. There is also preliminary evidence that euryha-line¯ounder Platichthys¯esus also adopt this mechanism of sodium uptake when adapted to freshwater (Clarke & Potts, 1998). The location of such pumps in ®sh gills, however, remains unclear, and may be associated with the pavement epithelial cells (Laurent, Goss & Perry, 1994;Sullivan, Fryer & Perry, 1995, 1996, the mitochondria rich cells (Lin & Randall, 1991) or both cell types (Lin & Randall, 1995).…”
Section: Introductionmentioning
confidence: 99%